Automatic Feeder for Laying Hens Based on Noise Amplitude - Rian Ferdian; Zaki Minango Dasman; Yan Heriyandi; Mohammad Hafiz Hersyah (JURNAL NASIONAL TEKNIK ELEKTRO, 2022)
Food is an essential aspect of the laying hens' cultivation process. The delay of the feeding time and the short amount of food can cause stress to the hens. Furthermore, an excessive amount of food can cause overweight and reduce hens' productivity. This paper provides a method to automate the feeder for laying hens using a device based on microcontroller technology. A tool that can detect chicken behavior when hungry and the temperature of the cage can provide an excellent feeding management system for the breeder. The automatic feeder can see chicken behavior, also the environmental condition around the cage. A specific noise amplitude caused by the hungry hens can trigger the feeder.  This feeder also design aims to provide the food in the right amount at the right time. Thus, the breeder can minimize the stress of laying hens, reduce food waste, and keep the hens ideal. Here the system can save the chicken’s food around 13.76% more efficient.